Things that float and things that don't - Adler, David A. (Holiday House, 2013)
"An apple floats in a tub of water, but a ball of aluminum foil sinks to the bottom. But wait. If that same ball of foil is flattened out and shaped into a boat, it floats! How can that be? David A. Adler's clear, concise text and Anna Raff's delightful illustrations explain the basic principles of flotation and density in a way that will really sink in"--Front dust jacket flap.